Investigating wound healing potential of Typha angustata L. inflorescence in albino Wistar rats - Shraddha Saha; Vibha Sonar; Bansari Soni; Shreya Koladiya; Sumitra Chakraborty; Meonis Pithawala (Elsevier, 2021)
Background: Typha angustata L. is a common aquatic weed. Although the folkloric use of Typha in wound healing has been reported, scientific evidences are still lacking. Purpose: The present study aimed to explore the wound healing potentials of T. angustata L. Method: The ointment was prepared from the aqueous extract of Typha inflorescence and applied on the induced wounds (viz., Excision, Incision and Burn) in albino Wistar rats. Continuous monitoring of percentage of wound contraction, epithelization duration, content of hydroxyproline and protein (from the excised wound tissues collected on 14th and 28th day of treatment) were used as parameters to know wound healing effects. In addition, catalase activity (antioxidant marker) and histopathological studies were also carried out. Results: Topical application of the test ointment showed significant (p<0.05) wound contraction, fast epithelization, increased hydroxyproline content and increased catalase activity in comparison to the reference drug treated groups [(treated with (10%w/w) povidone iodine and (10%w/w) burnol ointment)] as well as control groups (treated with ointment base) in all wound types. Similarly, the histopathological study also revealed better reparative changes in terms of neo-vascularization and collagen tissue deposition in treated animals as compared to reference drug treated and control group animals. Conclusion: The results of the present study suggest the potentials of Typha plant in formulating wound healing agents.